Workload and Stress Level in Non-COVID-19 Zoning Nurses at National Central Public Hospital Jakarta - Zakiyah, Zakiyah; Karim, Ulfah Nuraini; Dewi, Aliana; Nuraini, Siti; Sutandi, Aan; Alnur, Rony Darmawansyah (UI Scholars Hub, 2023)
The COVID-19 pandemic has increased the workload for nurses directly handling COVID-19 patients and those working in non-COVID-19 zones. As the number of COVID-19 cases rises, nurses face psychological problems, including stress. This study aimed to determine the relationship between workload and stress levels in a non-COVID-19 zoning ward using a cross-sectional approach and Spearman’s correlation test conducted on 94 nurses at one hospital in Jakarta, Indonesia, selected through simple random sampling. The workload questionnaire with 15 items and the DASS 42 questionnaire were used to measure stress levels. The results indicated that most nurses (73.4%) experienced a heavy workload. Regarding stress levels, most nurses (66%) reported severe stress, while a small number experienced mild (2.1%) and moderate stress (2.1%). The Spearman’s test revealed a significant relationship between workload and stress levels in the non-COVID-19 zoning ward (p-value = 0.001). Based on these findings, hospitals are urged to effectively manage nurses’ workload during the COVID-19 pandemic and implement specific interventions for nurses experiencing occupational stress.